Financialization and the rentier income share - evidence from the USA and Germany - Petra Dünhaupt (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
During the past two decades, there has been a shift of significance from the real to the financial sector. This development is often referred to as "financialization". Most industrial countries have experienced a decline in the share of labor income. Based on a review of empirics and literature, this paper seeks to determine who gained from the fall in the labor share of income in the USA and Germany, respectively. If financialization is indeed responsible for the decline, rentiers should be the beneficiaries. In order to identify the relevant effects, the profit share of the two countries under observation is split up between the share of retained earnings and the share of net property income (= rentiers' income). The presented evidence shows that the development of the rentier income share indeed corresponds quite well with the stages of development of financialization.
urn:nbn:de:101:1-201101312807
Keywords: E25; E44; 330; Financialization; income distribution; rentier income share; Finanzkapitalismus; Rententheorie; Gewinnquote; USA; Deutschland